STRATEGI PENGUATAN POSITIF DALAM MENINGKATKAN PERILAKU DISIPLIN ANAK USIA 4-5 TAHUN DI TK FLAMBOYAN PLATUK - Mira Handayani (Universitas Narotama, 2023)
This research seeks to reveal how to improve the disciplinary behavior of children aged 4-5 years, some of strategies used by Flamboyan Platuk Surabaya Kindergarten teachers in improving student discipline behavior is by applying positive reinforcement. This study aims to identify and describe strategies for giving positive reinforcement in improving the discipline behavior of children aged 4-5 years at Kindergarten Flamboyan Platuk Surabaya. This study uses a qualitative descriptive approach, taking place in Kindergarten Flamboyan Platuk Surabaya. The subjects in this study were the head of Kindergarten Flamboyan Platuk, group A2 teachers and group A2 students. The object of this study is a strategy of providing positive reinforcement in improving the discipline behavior of children aged 4-5 years at Kindergarten Flamboyan Platuk Surabaya. Data collection techniques were carried out through non-participant observation, unstructured interviews, and documentation. Data analysis techniques by collecting data, presenting data, and drawing conclusions. The results of this study indicate that the strategy of providing positive reinforcement in improving the discipline behavior of children aged 4-5 years in Kindergarten Flamboyan Platuk, namely: first, choosing an effective reinforcer. Second, make the reinforcer contingent and timely. Third, use the agreement. Keywords: Positive Reinforcement, Disciplined Behavior, Early Childhood